Rising lake levels in central East Africa are driven by increasing rainfall and land-use intensification - Aidan Byrne; Ken Norris; Michael A. Chadwick; Sean Avery; Lydia Olaka; Emma J. Tebbs (Journal of Hydrology: Regional Studies)
Study region: 375 lakes across the East African Rift System Study focus: East African Rift System lakes provide a critical region of freshwater biodiversity and support the livelihoods of millions of people. Since 2010, water levels have risen at many Kenyan Rift System lakes flooding settlements, destroying infrastructure and impacting biodiversity, whereas several Ethiopian lakes experienced declining water levels, threatening water availability. However, water storage changes have not been quantified and the drivers of hydrological change have not been assessed on a regional scale. Here, we used satellite Earth observation and open-access data products to quantify changes in lake water volumes, total catchment water storage anomalies and environmental drivers for 375 lakes across the East African Rift System from 2000 to 2023. New hydrological insights for the region: Water storage increased across central East Africa and declined in the south of the Rift System, with lake surface areas increasing by a total of 71,822 km2 and water volumes increasing by 1375.2 km3. Increasing rainfall (Coef = 1.775, SE = 0.571, p = 0.002) and urban development (Coef = 6.270, SE = 2.260, p = 0.006) caused expanding lake surface areas, whereas population growth within catchments reduced both lake surface areas (Coef = −7.023, SE = 2.210, p = 0.002) and water volumes (Coef = −8.735, SE = 3.578, p = 0.020). Increasing rainfall trends (Coef = 4.454, SE = 1.733, p = 0.020) and the expansion of catchment forest cover (Coef = 11.284, SE = 5.263, p = 0.047) facilitated greater water storage within lake basins. With more extreme wet seasons and longer dry seasons predicted for East Africa under climate change, sustainable catchment management is required to mitigate both future flooding and drought events.